The Road from AKI to CKD: Molecular Mechanisms and Therapeutic Targets of Ferroptosis - Runzhi Guo; Jiayu Duan; Shaokang Pan; Fei Cheng; Yingjin Qiao; Qi Feng; Dongwei Liu; Zhangsuo Liu (Cell Death and Disease, 2023)
Abstract Acute kidney injury (AKI) is a prevalent pathological condition that is characterized by a precipitous decline in renal function. In recent years, a growing body of studies have demonstrated that renal maladaptation following AKI results in chronic kidney disease (CKD). Therefore, targeting the transition of AKI to CKD displays excellent therapeutic potential. However, the mechanism of AKI to CKD is mediated by multifactor, and there is still a lack of effective treatments. Ferroptosis, a novel nonapoptotic form of cell death, is believed to have a role in the AKI to CKD progression. In this study, we retrospectively examined the history and characteristics of ferroptosis, summarized ferroptosis’s research progress in AKI and CKD, and discussed how ferroptosis participates in regulating the pathological mechanism in the progression of AKI to CKD. Furthermore, we highlighted the limitations of present research and projected the future evolution of ferroptosis. We hope this work will provide clues for further studies of ferroptosis in AKI to CKD and contribute to the study of effective therapeutic targets to prevent the progression of kidney diseases.